Analisis Pendapatan Masyarakat Desa untuk Kelestarian Hutan Lindung (Studi Hutan Desa Pattaneteang Kabupaten Bantaeng) - Sukardi Sukardi (Fakultas Kehutanan, Universitas Hasanuddin, 2017)
Average income of Pattaneteang rural community aren’t ideal. This condition is resulting land utilization of rural forest in preserved forest area to increase their income and threats the forest sustainability in both rural community. Therefore, it is necessary to note the influence from both rural community income either from inside nor outside the rural forest on community management land as one of the indicators of to preserved forest sustainability. The quantitative approach used in this research is used to analyze field and secondary data as comparative data. From the research it is know, the biggest Pattaneteang income is gain by using land outside the rural forest worth Rp. 14.060.500/Family/Year, while using land inside rural forest only worth Rp. 3.338.000/Family/Year. This income affects the community management land as an indicator of the condition of preservation of protected forest areas in both of the rural.